Inclusion through Participation: Fostering Pupils' Feelings of Belonging in Swedish After-School Care - Peter Ingemar Karlsudd (MDPI AG, 2023)
The guiding principle for after-school care is to avoid segregation and specialist solutions. However, a tendency to segregate children needing special support in Swedish after-school care is a reality. A significant problem that after-school care faces is maintaining inclusive activities. This study aims to map the problem and find methods to reduce segregating processes in after-school care. Based on interviews with after-school teachers and student teachers focusing on work in after-school centres, the aim is to paint a picture of the centres' current perspectives and efforts to create a sense of belonging for all children. In the analysis, a division of special pedagogy is used based on three discourses present in previous studies. As the results show, the interviewees advocated for an inclusive pedagogy. The scope, ambition, and prerequisites for this work varied between the different after-school centres, but all those interviewed agree that working with participation is the key to inclusion. The staff had a range of strategies and methods to ensure that all children in the organisation experienced a sense of belonging. The interviewees agreed that after-school centres should receive more resources and space for their after-school pedagogies to maintain an inclusive function.